Sliding Base Structures Analysis and Design - Hu, Hong-Song (Springer Nature, 2023)
This open access book is an efficient and economic approach for mitigating the seismic damage of low-rise buildings. This book presents various aspects of SB structures, including their fundamentals, dynamic analysis procedures, seismic response characteristics, design methods, and practical applications. It contains a comprehensive study on the influence of various structural and ground motion characteristics on the responses of SB structures, which is particularly helpful for the readers to fully understand the behavior of SB structures. Researchers and engineers in the field of structural engineering and earthquake engineering will benefit from this book.